Direct carbon dioxide hydrogenation to long-chain α-olefins over FeMnK catalysts - Ren, Hao; Yang, Haiyan; Xin, Jing; Wu, Chongchong; Wang, Hao; Zhang, Jian; Bu, Xianni; Yang, Guoming; Li, Jiong; Sun, Yuhan; Gao, Peng (Applied catalysis. B, Environmental, 2024)
The catalytic hydrogenation of CO2 to high-carbon linear α-olefins (LAOs; C ≥ 4) has gained considerable attention. In this study, FeMnK catalysts were synthesised using an organic combustion method. The introduction of Mn promoted the dispersion of Fe species and enhanced the formation of the iron oxides, whereas the introduction of K promoter led to the formation of iron carbides and improved the carbon chain-growth capability of catalysts. The mechanistic studies revealed that the addition of Mn and K regulated the matching of reverse water gas shift and subsequent Fischer–Tropsch synthesis reactions by enhancing the formation and further conversion of CO intermediate. The selectivity and productivity of LAOs were 45.7 % and 0.236 g∙gcat−1∙h−1, respectively, under the reaction condition of 320 °C, 2 MPa and 20000 mL∙gcat−1∙h−1. Furthermore, FeMn0.1K0.1 exhibited excellent stability for up to 160-h on stream, demonstrating promising industrial application prospects for CO2 conversion into value-added fuels and chemicals. [Display omitted] •Fe catalysts decorated with Mn and K for CO2 hydrogenation to linear α-olefins.•Mn promotes the dispersion of Fe species and enhances the formation of FeOy phases.•K promotes the formation of Fe5C2 and improves the carbon chain-growth capability.•Mn and K promoters regulate the matching of RWGS and subsequent FTS reactions.•The as-prepared FeMn0.1K0.1 exhibits the best performance with excellent stability.